0

# what is 0/3 simplified

Simplifying
x + 2 = 3x + -1x2 + 5

Reorder the terms:
2 + x = 3x + -1x2 + 5

Reorder the terms:
2 + x = 5 + 3x + -1x2

Solving
2 + x = 5 + 3x + -1x2

Solving for variable 'x'.

Reorder the terms:
2 + -5 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2

Combine like terms: 2 + -5 = -3
-3 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2

Combine like terms: x + -3x = -2x
-3 + -2x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2

Reorder the terms:
-3 + -2x + x2 = 5 + -5 + 3x + -3x + -1x2 + x2

Combine like terms: 5 + -5 = 0
-3 + -2x + x2 = 0 + 3x + -3x + -1x2 + x2
-3 + -2x + x2 = 3x + -3x + -1x2 + x2

Combine like terms: 3x + -3x = 0
-3 + -2x + x2 = 0 + -1x2 + x2
-3 + -2x + x2 = -1x2 + x2

Combine like terms: -1x2 + x2 = 0
-3 + -2x + x2 = 0

Factor a trinomial.
(-1 + -1x)(3 + -1x) = 0

### 1 Answer by Expert Tutors

Philip P. | Effective and Affordable Math TutorEffective and Affordable Math Tutor
5.0 5.0 (428 lesson ratings) (428)
0
Looks as if you almost got the right answer.  You did get the quadratic equation correct, but the standard way to write a quadratic equation is:

x2 - 2x - 3 = 0

When factored, you get:

(x-3)(x+1) = 0

You got

(-1+ -1x)(3+ -1x) = 0

You can factor a (-1) out of the first term and drop the coefficients of 1 in front of the x, since 1*x = x:

(-1)(x+1)(-x+3) = 0

Then multiply the (-1) across the second term and you get:

(x+1)(x-3) = 0

So the solutions are:

x = 3, -1

Not sure why you want to know what 0/3 is, but 0/3 = 0*(1/3) = 0